TINJAUAN MAQĀSID SYARĪAH TERHADAP PERKARA HARTA BERSAMA DAN KONTRIBUSINYA DALAM PEMBARUAN HUKUM KELUARGA ISLAM DI INDONESIA (Studi Kasus di Wilayah Hukum Pengadilan Tinggi Agama Bengkulu) - Imansyah, Zuhri; Jayusman, Jayusman; Pane, Erina; Efrinaldi, Efrinaldi; Fahimah, Iim (Universitas Islam Negeri Raden Intan Lampung, 2020)
The problem of joint property disputes after divorce in the jurisdiction of the Bengkulu Religious high courts, in the period 2010 to 2015 all decisions are always made up of half of the property of the ex-wife and the other half of the property of the ex-husband, regardless of who is more dominant in working to produce the property. This is based on article 97 of the Islamic Law Compilation. According to the authors the decisions did not fulfill a sense of justice, with regard to wives who participated in working for a living. The judges of the first level Religion Court in Bengkulu did not consider the role of the wife working for a living; which incidentally is the husband's obligation. How does the Maqāsid asy-Syarī'ah review the Bengkulu judges' consideration of joint property in the case of a wife participating in earning a living in the jurisdiction of the Bengkulu’s Religious high courts? and What are the implications of the judge's decision in the jurisdiction of the Bengkulu’s Religious high courts regarding joint property in the case of the wife participating in earning a living in the context of Islamic family law reform in Indonesia? The conclusions of this research are: Judges' considerations on decisions regarding joint assets in the case of wives participating in earning a living in the jurisdiction of the Bengkulu Religious high courts were not in accordance with Maqāsid asy-Syarī'ah, because the judge did not consider the position of his ex-wife who continued to work for a living besides running obligation to take care of the household. The judge's decision regarding joint property in the case of his wife helped earn a living in the jurisdiction of the Bengkulu Religious high courts in the context of reforming the Islamic Family Law in Indonesia, the judge must be progressive. The ex-wife who helped make a living should get a share of the joint property that is greater than the ex-husband. The ex-wife's portion was formulated peacefully and deliberately between the parties.